Preliminary Report on Race and Washington's Criminal Justice System - Race and the Criminal Justice System, Task Force On (2011)
For this Report, the Research Working Group reviewed evidence on disproportionality in Washington’s criminal justice system and considered whether crime commission rates accounted for this disproportionality. We found that crime commission rates by race and ethnicity are largely unknown and perhaps unknowable, but that some researchers simply take arrest rates as good proxies for underlying commission rates for all crimes.We found that use of arrest rates likely overstates black crime commission rates for several reasons.68 But even if arrest rates are used as a proxy for underlying crime commission rates, the extent of racial disproportionality is not explained by commission rates. In 1982, 80% of black imprisonment in Washington for serious crimes could not be accounted for based on arrest rates, though by 2009, this had dropped to 45%Part II presents the Working Group’s findings and data regarding racial disproportionality within Washington State’s criminal justice system. Part III discusses three possible causes for this disproportionality. Part III.A discusses differential commission rates, concluding that this factor alone cannot account for the disproportionality observed in the criminal justice system. Part III.B discusses seven racially neutral policies that have racially disparate effects, and thus help explain racial disproportionality. Finally, Part III.C discusses bias, whether explicit or implicit, and how it produces racial disparity